Georgian Dictionary of Public Health (GDPH) — First Electronic Edition, Version 1.0 - Giorgi Pkhakadze (Georgian Medical Journal, 2026)
The Georgian Dictionary of Public Health (GDPH) is the first comprehensive bilingual Georgian–English public health terminology reference, developed over two decades under the editorial direction of Prof. Giorgi Pkhakadze at the Public Health Institute of Georgia (PHIG) and the Georgian Medical Journal (GMJ). The First Electronic Edition (Version 1.0) contains 12,597 terms organised across 18 subject domains, including epidemiology, biostatistics, health policy and governance, health economics, infectious disease and immunisation, environmental health, health promotion, quality and patient safety, maternal and child health, mental health, global health, bioethics, digital health, and clinical–public health boundary terms. Terminological sources include ICD-11 for Mortality and Morbidity Statistics (WHO, 2024), Medical Subject Headings (NLM, 2024), the ISI Glossary (Pkhakadze, 2019), and Georgian national health legislation (matsne.gov.ge). Each entry provides a Georgian headword, authoritative Georgian definition, plain-language explanation, Georgian everyday example, statement of practical relevance, and minimum three Vancouver-format references. 141 terms are directly anchored to Georgian national health legislation. 11,533 cross-links connect related entries. The dictionary is published open access under Creative Commons Attribution 4.0 International (CC BY 4.0). Keywords: bilingual dictionary; public health terminology; Georgian language; epidemiology; ICD-11; Medical Subject Headings; open access; Georgian health legislation; health systems; GDPH; Georgian Medical Journal